Overexpressing PpBURP2 in Rice Increases Plant Defense to Abiotic Stress and Bacterial Leaf Blight - Yu, Shunwu; Yang, Fangwen; Zou, Yuqiao; Yang, Yunan; Li, Tianfei; Chen, Shoujun; Wang, Yulan; Xu, Kai; Xia, Hui; Luo, Lijun (Frontiers in Plant Science, 2022)
Mosses are one of the earliest diverging land plants that adapted to living on land. The BURP domain-containing proteins (BURP proteins) are plant-specific proteins that appeared when plants shifted from aquatic environments to land. Phylogenetic analysis revealed that the BURP domain of higher plants is originated from lower land plants and divergent because of motif conversion. To discover the function of BURP protein in moss, rice transgenics with ectopic expression of PpBURP2 were subjected to different abiotic stresses treatments. The results revealed that the ectopic expression of PpBURP2 enhanced the tolerance to osmotic and saline stresses at the seedling stage and drought stress at the adult stage. Further ectopic expression of PpBURP2 improved the cadmium (2+) (Cd2+) tolerance and reduced Cd2+ accumulation in rice leaves. Transcriptomic analysis of the transgenic PpBURP2 plants showed that the differentially expressed genes were involved in the metabolism of secondary metabolites, energy, oxidation-reduction process, and defense-related genes. Further experiments showed that the photosynthetic efficiency and resistance against bacterial leaf blight were obviously improved in transgenic plants. Yeast two-hybrid and bimolecular fluorescence complementation (BiFC) assays revealed the physical interaction of BURP domain protein from rice and moss with mitogen-activated protein kinase kinase (MKK) from rice. Therefore, our findings demonstrate that overexpressing PpBURP2 in rice confers resistance to abiotic stresses and bacterial leaf blight. They also suggested that the regulatory role of BURP-like proteins across lower and higher plants was evolutionary conservation of responses of different classes of plants to different environmental challenges.